The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/jsfa.11003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibers fractionated from gardenia (Gardenia jasminoides Ellis) husk: structure and in vitro hypoglycemic effect

Abstract: BACKGROUND Gardenia (Gardenia jasminoides Ellis) husk rich in dietary fiber is a byproduct of fructus processing, and commonly discarded as waste. The husk was fractionated by sequential extraction into four fractions: water‐soluble fiber (W‐SF), acid‐soluble fiber (Ac‐SF), alkali‐soluble fiber (Al‐SF) and insoluble residue fiber (IRF). The aim of this study was to investigate the differences in structure and in vitro hypoglycemic effect of these fibers. RESULTS Monosaccharide composition and Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The result was consistent with the previous study ( Wandee, Uttapap, & Mischnick, 2018 ). By contrast, C-SDF had the lowest content of pectin, resulting from the slight destruction of acid to the bond of pectin with the cell wall ( Meng, Wu, Liu, Tang, & Nie, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The result was consistent with the previous study ( Wandee, Uttapap, & Mischnick, 2018 ). By contrast, C-SDF had the lowest content of pectin, resulting from the slight destruction of acid to the bond of pectin with the cell wall ( Meng, Wu, Liu, Tang, & Nie, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ancient Compendium of Materia Medica documents Zhizi ’s dual role in shelling or removing shells to treat different diseases ( Li, 1996 ). Recent research reveals that the pericarp of Gardeniae Fructus is a potent source of dietary fibers and exhibits hypoglycemic properties ( Meng et al., 2021 ). Findings from this study indicated that Zhizi ’s flesh and seeds contain higher concentrations of iridoids and pigments, while organic acids and flavonoids are predominantly present in its pericarp.…”
Section: Discussionmentioning
confidence: 99%
“…The WS was determined according to the previous method with minor modification (Meng et al ., 2021). Samples (0.5 g) were mixed with 20 mL of distilled water and stirred in a water bath for 30 min at 90 °C using a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%